3plex Web: An interactive platform for RNA:DNA triplex prediction and analysis - Marco Masera; Chiara Cicconetti; Francesca Ferrero; Salvatore Oliviero; Ivan Molineris (Computational and Structural Biotechnology Journal)
Long non-coding RNAs (lncRNAs) exert their functions by cooperating with other molecules, including proteins and DNA. Triplexes, formed through the interaction between a single-stranded RNA (ssRNA) and a double-stranded DNA (dsDNA), have been consistently described as a mechanism that allows lncRNAs to target specific genomic sequences in vivo. Building on the computational tool 3plex, we developed 3plex Web, an accessible platform that enhances the prediction of RNA:DNA triplexes by integrating interactive visualization, statistical evaluation, and user-friendly downstream analysis workflows. 3plex Web implements new features such as input randomization for statistical assessments, interactive profile plotting for triplex stability, and customizable DNA Binding Domain (DBD) selection. This platform enables rapid analysis through PATO, substantially reducing processing times compared to previous methods, while offering Snakemake workflows to integrate gene expression data and explore lncRNA regulatory mechanisms.